Anemia dan Kek pada Ibu Hamil dengan Kejadian Berat Badan Lahir Rendah - Edni Wari, Fitria; Khasanah, Nurun Ayati; Putri Noviliansari, Pangesti (Universitas Islam Jember, 2025)
Seventy percent of infant deaths in low-income countries are due to Low Birth Weight (LBW). Factors like the mother's nutrition, specifically Chronic Energy Deficiency (CED) and Anemia, contribute to LBW. This study looked at how Anemia and CED in pregnant women relate to LBW. This analytical observational study used a cross-sectional approach with all pregnant women who had given birth in the Bubakan Health Center Work Area. Sampling was done using total sampling. Statistical tests with the Chi Square test. Secondary data collection from the birth report book. The results showed that most respondents did not experience anemia (55.1%), most respondents did not have CED (52.2%) and half of respondents were not born with LBW (50.7%). Almost half of anemic mothers gave birth to LBW babies, namely 25 respondents (36.2%). Approximately half of the mothers with anemia gave birth to LBW infants, namely 26 respondents (37.7%). The results of the Chi Square test showed a ρ-value = 0.000 so that there is a relationship between anemia and KEK in pregnant women with LBW. Poor nutrition during pregnancy negatively impacts fetal growth, raising the chance of LBW. Midwives can improve nutritional support to reduce LBW rates in their communities.